2022
DOI: 10.1038/s41440-021-00819-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sacubitril/valsartan versus olmesartan in Japanese patients with essential hypertension: a randomized, double-blind, multicenter study

Abstract: This phase III study assessed the efficacy and safety of sacubitril/valsartan compared with those of olmesartan in Japanese patients with essential hypertension. Patients (n = 1161, aged ≥20 years) with mild to moderate hypertension (mean sitting systolic blood pressure [msSBP] ≥150 to <180 mmHg) were randomized to receive sacubitril/valsartan 200 mg (n = 387), sacubitril/valsartan 400 mg (n = 385), or olmesartan 20 mg (n = 389) once daily for 8 weeks. The primary assessment was a reduction in msSBP from ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 35 publications
0
43
0
3
Order By: Relevance
“…Even when we set the cost at ¥20,000/month, the ICER was approximately ¥3.5 million/QALY, still under the threshold value of ¥5 million/QALY ( Figure 2 ). Recently, sacubitril/valsartan (angiotensin receptor-neprilysin inhibitor), a novel antihypertensive drug, was approved for hypertension management in Japan 34 , with a medication cost of ¥6,057 ($52.67) to ¥12,114 ($105.34) /month. Thus, the DTx cost we set around ¥10,000/month as the default might be a reasonable value according to the current simulation model.…”
Section: Discussionmentioning
confidence: 99%
“…Even when we set the cost at ¥20,000/month, the ICER was approximately ¥3.5 million/QALY, still under the threshold value of ¥5 million/QALY ( Figure 2 ). Recently, sacubitril/valsartan (angiotensin receptor-neprilysin inhibitor), a novel antihypertensive drug, was approved for hypertension management in Japan 34 , with a medication cost of ¥6,057 ($52.67) to ¥12,114 ($105.34) /month. Thus, the DTx cost we set around ¥10,000/month as the default might be a reasonable value according to the current simulation model.…”
Section: Discussionmentioning
confidence: 99%
“…[86][87][88][89] Other sodium-excerting drugs such as angiotensin receptor-neprilysin inhibitors (ARNI) and sodium-glucose co-transporter 2 (SGLT2) inhibitors, both of which are proven therapies for heart failure, are also effective in lowering BP. [90][91][92][93][94][95][96][97] SGLT2 inhibitors also decrease 24-hour BP in patients who have both diabetes and hypertension. [98][99][100][101] ARNI have recently been launched for the treatment of hypertension in Japan and China.…”
Section: Choice Of Preferred Antihypertensive Agentsmentioning
confidence: 99%
“…The detailed characteristics of 16 studies (10,19,20,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) are shown in Table 1. Most of the data are come from ClinicalTrials.gov, 14 trials are multi-center and 12 trials are aimed at patients with HF.…”
Section: Study Characteristicsmentioning
confidence: 99%